Confirmatory Factor Analysis (CFA) for the instrument of personality, safety climate and safety performance in the Malaysia manufacturing sector - Mat Jusoh, Nurul Hidayu; Panatik, Siti Aisyah; Adam Assim, Mohd Ibrani Shahrimin; Yaacob, Yasmin; Zulikifli, Nurul Nadwa (Human Resource Management Academic Research Society, 2021)
This paper aims to draw on the application of Confirmatory Factor Analysis (CFA) in Structural Equation Modeling (SEM), to test the validity and reliability of instruments in the study of personality, safety climate, and safety performance in the Malaysia manufacturing sector. Exploratory factor analysis (EFA) was employed to determine the best sub-factors and items for the instrument, while confirmatory factor analysis (CFA) was performed to test and validate the measurement model. Confirmatory Factor Analysis (CFA) using Structural Equation Modeling (SEM) Partial Least Square (PLS), has been used to test the validity and reliability of the instruments. Various tests i.e., construct validity analysis, construct reliability, validity convergent as well as discriminatory validity to filter the best items that can represent the constructs in the study. Results from CFA indicated that two items from the Safety Performance Scale (SPS) had to be discarded to confirm that the model was fit. Meanwhile, all items from the Safety Climate Scale (SCS) and Mini-International Personality Item Pool (IPIP) were maintained. Overall, the final version of the instrument consisted of Safety Climate Instruments (46 items), Big Five Personality Instruments (20 items), and Safety Performance Instruments (37 out of 39 items).